The long step back. A path toward the enhancement of an extraordinary tool to fight mafia-style organized crime. (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
The scholar of the mafia phenomenon is called with increasing frequency to confront the resilience of the instruments of aggression and prevention that have made it possible to stem the expansion of organized crime. In this contribution, therefore, the special detention regime regulated by Article 41 bis of the Penitentiary Order, with respect to which recent pronouncements by the high courts have fueled a heated political and social debate, is examined.
Keywords: mafia; art. 41 bis; special detention regime; cooperation with justice; hard prison